The lipid biochemistry of eukaryotic algae. (April 2019) - Li-Beisson, Yonghua; Thelen, Jay J.; Fedosejevs, Eric; Harwood, John L.
Abstract: Algal lipid metabolism fascinates both scientists and entrepreneurs due to the large diversity of fatty acyl structures that algae produce. Algae have therefore long been studied as sources of genes for novel fatty acids; and, due to their superior biomass productivity, algae are also considered a potential feedstock for biofuels. However, a major issue in a commercially viable "algal oil-to-biofuel" industry is the high production cost, because most algal species only produce large amounts of oils after being exposed to stress conditions. Recent studies have therefore focused on the identification of factors involved in TAG metabolism, on the subcellular organization of lipid pathways, and on interactions between organelles. This has been accompanied by the development of genetic/genomic and synthetic biological tools not only for the reference green alga Chlamydomonas reinhardtii but also for Nannochloropsis spp. and Phaeodactylum tricornutum. Advances in our understanding of enzymes and regulatory proteins of acyl lipid biosynthesis and turnover are described herein with a focus on carbon and energetic aspects. We also summarize how changes in environmental factors can impact lipid metabolism and describe present and potential industrial uses of algal lipids.